SƠ ĐỒ VI PHÂN VÙNG ĐỘNG ĐẤT THÀNH PHỐ HÀ NỘI TRÊN CƠ SỞ CÁC KẾT QUẢ ĐO DAO ĐỘNG VI ĐỊA CHẤN - Hùng, Nguyễn Tiến; LIANG WEN, KUO- (Vietnam Journal of Earth Sciences, 2011)
Seismic microzoning map of Hanoi city on the basis of microtremor motion observationsIn this study, seismic microzoning maps of Hanoi city are constructed on the basis of microtremor motion observations at 93 points. The ground predominant periods were determined from the horizontal to vertical (h/v) spectral ratios of microtremor motions. A microzonation map was constructed from the variation analysis of predominant periods by space. The result indicated that the predominant period of the study area increased from north to south and from west to east. The largest predominant period, larger than 1.2s, is found in the eastern part of this study area. In contrast, the lowest predominant period, less than 0.6s, is found in the northern part. Moreover, the results also showed that the study area can be divided into two categories: class C is distributed on the northern and western areas, while class D is distributed along the Red River, metropolitan, the eastern and the southern areas.